Indicators for an extended length of stay in the emergency service unit of a Thai community hospital: A multi-level analysis (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Extended length of stay affects the efficiency of patient care and results in undesirable patient outcomes. This study explores potential indicators for a prolonged length of stay in the emergency unit in a community hospital setting.Methods: A retrospective cohort study was conducted. Patients who visited the emergency unit during the first half of September 2018 were included. A multivariable multi-level risk regression was used to explore for potential indicators of an extended length of stay in the emergency unit.Results: A total of 1,160 emergency visits nested within 16 days study period were included for analysis. 126 (10.9%) visits with an extended length of stay (≥4 hours) and 1,034 visits with a length of stay less than 4 hours were identified. Different patient characteristics and characteristics related to emergency unit between groups were explored. Male gender (RR=1.52, 95% CI; 1.05-2.20, p=0.025), elderly patients (RR=1.82, 95% CI; 1.08-3.04, p=0.016), Burmese citizenship (RR=1.72, 95% CI; 1.15-2.59, p=0.009), non traumatic mode of presentation (RR=2.50, 95% CI; 1.28-4.92, p=0.008), hospital admission as disposition status (RR=2.38, 95% CI; 1.50-3.77, p